PERAN KEPALA MADRASAH DALAM MENINGKATKAN PERILAKU ORGANISASI LEMBAGA PENDIDIKAN ISLAM - Wawan Abdullah; M. A Tihami; Agus Gunawan (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Islamic educational institutions like Madrasah Tsanawiyah have a status comparable to elementary schools. The less effective role of madrasa heads in organisational behaviour weakens the Islamic education management process. This research aims to determine the role of madrasah heads in improving organisational behaviour. The research used qualitative methods with a case study approach at Madrasah Tsanawiyah Darul Mustafa Lebak Banten. Data collection uses interviews, observation and literature study. The analysis uses data triangulation. Research findings show that the role of the madrasa head achieves organisational behaviour, namely with a democratic leadership type through coaching, support, advice and motivation. Decision-making is taken through daily and plenary meetings considering the majority vote—leadership success through effective networking, communication, and collaboration. The role of the madrasa head improves organisational behaviour through leadership type, decision making and leadership success. The research implication is that the better the role of the madrasa head in organisational behaviour, the better the educational management of Islamic institutions.